Genome-wide analysis of genes involved in efflux function and regulation within Escherichia coli and Salmonella enterica serovar Typhimurium. Issue 2 (6th February 2023) - Holden, Emma R.; Yasir, Muhammad; Turner, A. Keith; Wain, John; Charles, Ian G.; Webber, Mark A.
Abstract : The incidence of multidrug-resistant bacteria is increasing globally, with efflux pumps being a fundamental platform limiting drug access and synergizing with other mechanisms of resistance. Increased expression of efflux pumps is a key feature of most cells that are resistant to multiple antibiotics. Whilst expression of efflux genes can confer benefits, production of complex efflux systems is energetically costly and the expression of efflux is highly regulated, with cells balancing benefits against costs. This study used TraDIS- Xpress, a genome-wide transposon mutagenesis technology, to identify genes in Escherichia coli and Salmonella Typhimurium involved in drug efflux and its regulation. We exposed mutant libraries to the canonical efflux substrate acriflavine in the presence and absence of the efflux inhibitor phenylalanine-arginine β-naphthylamide. Comparisons between conditions identified efflux-specific and drug-specific responses. Known efflux-associated genes were easily identified, including acrAB, tolC, marRA, ramRA and soxRS, confirming the specificity of the response. Further genes encoding cell envelope maintenance enzymes and products involved with stringent response activation, DNA housekeeping, respiration and glutathione biosynthesis were also identified as affecting efflux activity in both species. This demonstrates the deep relationship between efflux regulation and other cellular regulatory networks. We identified a conserved set of pathways crucial for efflux activity in these experimental conditions, which expands the list of genes known to impact on efflux efficacy. Responses in both species were similar and we propose that these common results represent a core set of genes likely to be relevant to efflux control across the Enterobacteriaceae.